(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s
(3ChdgG (B:s
(3GdHZi CjVkG GdaGLQI , MQI cGfJ Ch CeI , hai GdJfRjd (B: (3heG cGfJ Cec HZjG s
(3BNQgG (B:s
(3ef aUd GdbGa hGdWGA hGdfhf , bhdg (B: (3GdefWbI hGdfWGb cdeG TO Hg hSWg aEf QShd Gddg Udi Gddg Ydjg hSde bO NVH s
(3fSNI MGOjI YTQI HgG CKQ WeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B212 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ , HgG NQe s
(3GdfSNI HgG JdhjK s
Keywords: (3GddZIs